The Instructional Design of Technology and Mathematic Based Teaching for Basketball Materials Elementary School Students - Kurniadi, Ahmad; Iyakrus, Iyakrus; Bayu, Wahyu Indra; Yusfi, Herri; Usra, Meirizal; Syafaruddin, Syafaruddin (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2023)
Education is the most basic thing to build someone’s character because the aim of education is changing someone towards a better way. Education is a continuous and never-ending process so that it will produce sustainable quality, which the aimed is to build a person character in the future. Learning basketball is not only helpful to improve physical skills, such as; hand-eye coordination, physical endurance, and dexterity, but also teaching the important values, such as; cooperation, communication, and discipline. It can involve strategy, analysis, and mathematical understanding. As technology advances, the integration of technology and mathematics in learning process becomes really important. This research was conducted by applying technology and mathematic-based design to learn PJOK basketball materials at Elementary School number 81 Palembang. This research used an Equivalent Time Series Samples Design which is measured using skill tests and Formative Class Evaluation (FCE) questionnaires at the end of learning. The sample was 32 students at fifth graders at the Elementary School number 81 Palembang. The results obtained by the learning design show the poor category. The Formative Class Evaluation (FCE) questionnaire shows the result with a good component category, the willingness component is in the good category, the method component is in the medium category and the cooperation component is in the medium category.